Intestinal parasites in wild ungulates, lungworms (Metastrongylus spp.) and Trichinella spp. in wild boar in Portugal - Martins, Filipa Alexandra Lopes (2023)
Parasites can cause/predispose wild ungulates to disease but the presence of parasites does not necessarily mean that wildlife is unhealthy. Wildlife parasitology can offer insights into One Health, a growing overlap of habitats between domestic and wild ungulates can favour the spill-over of parasites between species and humans through environmental contamination. There are still few studies on the occurrence of parasites in wild ungulates. This study aimed to evaluate the diversity and burden of gastrointestinal parasites in wild ungulates and the presence of Trichinella spp. in wild boar in Portugal. Between 2020 and 2022, faecal and muscle samples of wild ungulates were collected in national hunting campaigns in 25 locations in the three regions of mainland Portugal. Samples of faeces collected from wild boar, deer and fallow deer were analysed using Mini-Flotac® and samples of the diaphragm or masseter muscle from wild boar were analysed by the magnetic stirrer method for pooledsample digestion. In total 263 faecal samples were collected. The presence of parasites was identified in 19.0% (34/179), 22.9% (16/70) and 50.0% (7/14) of wild boar, red deer and fallow deer, respectively. Eleven different parasites were identified, the most frequent being the strongyles (9.9%, 26/263). The potentially zoonotic parasites identified were Metastrongylus spp. (6.5%, 17/263), Trichuris spp. (1.5%, 4/263) and Ascaris suum (1.7%, 3/263). Concerning the parasite burden, it was very low with the highest burden being 95 eggs of strongyles per gram of faeces. Regarding the muscle samples, 149 wild boars were analysed and all samples tested negative, thus making their consumption safe, especially for private use. This epidemiological study allows us to obtain useful information to assess the health of these wild populations and potential risks from a One Health perspective. Although a considerable diversity of parasites was found, the burdens were low as well as the occurrence of zoonotic parasites. Public perception of wildlife diseases, if not uniformly framed and communicated, what can pose a threat to wildlife conservation, to wildlife itself, and therefore to LIFE on the planet.